2023
DOI: 10.3390/ani13071138
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Muscle Lipogenic Gene Expression, Carcass Traits and Fat Deposition among Three Iberian Pig Strains Finished in Two Different Feeding Systems

Abstract: The Iberian pig breed includes several well-differentiated strains. The present study evaluated carcass traits, fat deposition and muscle expression of important lipogenic genes (SCD, ME1, ACACA, FASN, EGR1, ACOX and ACLY) using 65 male pigs of 3 Iberian strains (20 Lampiño, 23 Torbiscal, and 22 Retinto) finished either in a conventional, concentrate-based system (CF) or in montanera (MF), a traditional free-range system with acorn feeding. Torbiscal had the highest ham, Longissimus thoracis and prime cuts yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 56 publications
4
2
0
Order By: Relevance
“…Our findings indicate that in spite of the similar IMF content in the NT, ST and NE loins, some differences in muscle fatty acids may occur. This observation is in agreement with that of Garrido et al [46], who found differences in the FA composition of Lampiño, Torbiscal and Retinto pigs despite similar IMF contents. The higher PUFA content in the NT loin suggests that it may probably be more susceptible to lipid oxidation compared to the ST and NE loins.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings indicate that in spite of the similar IMF content in the NT, ST and NE loins, some differences in muscle fatty acids may occur. This observation is in agreement with that of Garrido et al [46], who found differences in the FA composition of Lampiño, Torbiscal and Retinto pigs despite similar IMF contents. The higher PUFA content in the NT loin suggests that it may probably be more susceptible to lipid oxidation compared to the ST and NE loins.…”
Section: Discussionsupporting
confidence: 93%
“…The AI and TI in the NT loin were lower than those of the NE and ST loins as a result of the decrease in C16:0 and the increase in the total PUFA. Nevertheless, the range of AI and TI observed in this study was in line with those observed in several native pig breeds [41,45,46].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The FASN gene encodes the Fatty Acid Synthase, a multi-enzyme protein involved in the de novo synthesis of C16:0 from acetyl-CoA and malonyl-CoA. Additionally, it plays a role in the synthesis of long-chain SFAs [ 59 , 60 ]. Previous studies have investigated the relationship between higher expression of FASN and an increased risk of obesity due to the accumulation of triacylglycerols in humans [ 61 ].…”
Section: Resultsmentioning
confidence: 99%